(untitled) (Fiep Bulletin - online, 2013)
The objective of this work is to conduct a literature review on research in the field of cultural studies and on the possibilities of the use of photographs as a source of such research, with the object the sport and leisure. Results from the need to establish methodological and conceptual references to a study, still in development, about the culture of body movement, using photographs as a source of data recovered, preserved and digitized by the Collection of Memories of the infamous ESEFUFPEL. Being vast and controversial, it is essential to carry out a cut in the study conducted here. Focus our thinking in addressing the cultural studies that are based on the Marxist social criticism because, from a political perspective, we recognize the impossibility of scientific neutrality and impartiality. We believe that the use of photographs as a source for research on the culture of human movement may, as in other areas was proven to be possible, to enlarge our understanding of the representations, the meanings and social values produced and played on this type of human activity.